Model of Customer Value and Purchase Decision Analysis - Udin Ahidin; Wikrama Wardana; Rini Astuti; Lusiah Lusiah (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study investigates the relationships among product, distribution, promotion, customer value, and purchasing decisions in the lightweight brick industry in Jakarta, Indonesia. The research addresses a gap in the construction materials marketing literature by examining the mediating role of customer value in linking marketing mix variables to purchasing decisions. A descriptive and explanatory survey design was employed, involving 295 managers from construction and property companies selected from a population of 964 firms in DKI Jakarta. Data were analyzed using Structural Equation Modeling (SEM) with LISREL 8.70. The findings indicate that distribution and promotion significantly contribute to customer value and purchasing decisions, while customer value exerts a strong positive effect on purchasing decisions. The model explains 47% of the variance in customer value and 81% of the variance in purchasing decisions, demonstrating substantial explanatory power. Among the examined variables, customer value emerges as the most influential determinant of purchasing decisions, highlighting its strategic importance in the lightweight brick market. These findings suggest that firms should prioritize strategies that enhance customer value through effective distribution and promotional activities to strengthen market competitiveness and improve customer purchasing outcomes. This study contributes to the marketing literature by providing empirical evidence on the role of customer value as a key mechanism through which marketing activities influence purchasing decisions in the construction materials sector.